Does potassium silicate reduce wheat blast in young and adult wheat plants? - Bergmann-Martins, Mireli; da Silveira Lorenset, Mateus; Canabarro, Raissa; Rodrigues Liska, Gilberto; Silva Canuto de Pinho, Renata; Antunes da Cruz, Maria Fernanda (Revista Ceres, 2024)
Considering the different levels of efficiency reported in the literature for the use of potassium silicate (PS) on wheat blast, this work investigated whether the foliar spray of PS could reduce blast severity in young and adult wheat cultivars and increase wheat yield indexes. At 28 days after emergence, the ‘BR 18’, ‘BRS 208’, and ‘BRS Louro’ plant cultivars were sprayed with the following PS rates (g/L): 0, 5, 10, 20, and 25. Twenty-four hours after PS application, the plants were inoculated with 105 conidia/mL of P. oryzae. Seven days after the inoculations the blast severity in the control plants of the ‘BRS Louro’, ‘BR 18’, and ‘BRS 208’ cultivars were 85%, 60% and 35%, respectively. For the 5g/L (PS) dose, severity was reduced more than 60% in the three cultivars. Adult plants of the ‘BRS 208’ and ‘BRS Louro’ cultivars were sprayed with water (control) or PS (20g/L) at the tillering, booting, and inflorescence stages. The PS applications were not efficient at reducing blast severity in adult plants and did not affect the wheat yield indexes. PS is only efficient at reducing blast severity in young plants.